Extracellular matrix allows PC12 neurite elongation in the absence of microtubules (The Rockefeller University Press, 1990)
Several groups have shown that PC12 will extend microtubule-containing neurites on extracellular matrix (ECM) with no lag period in the absence of nerve growth factor. This is in contrast to nerve growth factor (NGF)-induced neurite outgrowth that occurs with a lag period of several days. During this lag period, increased synthesis or activation of assembly-promoting microtubule-associated proteins (MAPs) occurs and is apparently required for neurite extension. We investigated the growth and microtubule (MT) content of PC12 neurites grown on ECM in the presence or absence of inhibitors of neurite outgrowth. On ECM, neurites of cells with or without prior exposure to NGF contain a normal density of MTs, but frequently contain unusual loops of MTs in their termini that may indicate increased MT assembly. On ECM, neurites extend from PC12 cells in the presence of 10 microM LiCl at significantly higher frequency than on polylysine. On other substrates, LiCl inhibits neurite outgrowth, apparently by inhibiting phosphorylation of particular MAPs (Burstein, D. E., P. J. Seeley, and L. A. Greene. 1985. J. Cell Biol. 101:862-870). Although 35-45% of 60 Li(+)-neurites examined were found to contain a normal array of MTs, 25- 30% were found to have a MT density approximately 15% of normal. The remaining 30% of these neurites were found to be nearly devoid of MTs, containing only occasional, ambiguous, short tubular elements. We also found that neurites would extend on ECM in the presence of the microtubule depolymerizing drug, nocodazole. At 0.1 micrograms/ml nocodazole, cells on ECM produce neurites that contain a normal density of MTs. This is in contrast to the lack of neurite outgrowth and retraction of extant neurites that this dose produces in cells grown on polylysine. At 0.2 microgram/ml nocodazole, neurites again grew out in substantial number and four of five neurites examined ultrastructurally were found to be completely devoid of microtubules. We interpret these results by postulating that growth on ECM relieves the need for MTs to serve as compressive supports for neurite tension (Dennerll, T. J., H. C. Joshi, U. L. Steel, R. E. Buxbaum, and S. R. Heidemann. 1988. J. Cell Biol. 107:665). Because compression destabilizes MTs and favors disassembly, this would tend to increase MT assembly relative to other conditions, as we found. Additionally, if MTs are not needed as compressive supports, neurites could grow out in their absence, as we also observed.